Margaret Chase Smith Library 2014 Student Essay Contest: Changes in the United States over the Last 50 Years - Abraham, Jonah (Maine Policy Review, 2014)
Each year, the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The 2014 essay prompt asked students to reflect on the changes the nation has undergone—politically, economically, technologically, and culturally—over the past 50 years since 1964, when Margaret Chase Smith announced her candidacy for the Republican presidential nomination. Maine Policy Review features here the second place 2014 prize-winning essay.